The relationship between technical and tactical elements of direct points with regard to the qualifications for the 2018 volleyball women's world championship - Momcilovic, Z.; Markovic, S.; Vicentijevic, A.; Nešic, G.; Bogavac, D.; Milosavljevic Dukic, T. (Facta Universitatis: Series Physical Education and Sport, 2019)
The goal of this paper is to analyse the relationships and differences among volleyball teams, participants of the 2018 World Cup in Japan, divided into three categories by their final standings (1st to 4th place, 5th to 8th place and others), based on the elements of situation-based efficiency. For the purposes of this paper, information from the official match reports (p 2 report) related to the way of winning points in the match was used, and these data were analysed using the program Volleyball Information System (VIS). The data obtained were analysed in relation to the team category and the outcome of the match. The data were obtained using descriptive and comparative statistical procedures. The survey sample includes all the women`s volleyball championship games played in Japan in 2018. Based on the final standings, the teams were divided into three groups: 1) the teams who reached the 3rd stage of the tournament (6 teams, from 1st to 6th place); 2) the teams that finished the competition in phase 2 (10 national teams, ranking 7th to 16th); 3) national teams that finished the competition in phase 1 (8 national teams, ranking 17th to 24th). The results obtained indicate that the teams had an equally good performance of the block and serve game elements; statistically these were not significant for the match outcome, but they rather serve as an aid for the overall game and for the final outcome of the match. The results of this research also highlight the spike as the key element affecting the positive end result of the match. It is important to emphasize that the opponent errors are a factor that depends exclusively on the opponent, but they also determine the overall score of the winning team.